Matematyka
pink32451
2017-06-25 14:52:54
Porównaj liczby a) a= pierwiastek z 6 +2 b=2- pierwiastek z 3
Odpowiedź
nobody5
2017-06-25 16:09:42

SPOSÓB I [latex]a= sqrt{6} +2\ b=2- sqrt{3}\\ cfrac{a}{b}=cfrac{sqrt{6} +2}{2- sqrt{3}}=cfrac{(sqrt{6} +2)(2+ sqrt{3})}{(2- sqrt{3})(2- sqrt{3})}=cfrac{(sqrt{6} +2)(2+ sqrt{3})}{4-3}=\\\ =(sqrt{6} +2)(2+ sqrt{3})\\ sqrt{6} +2 extgreater 1 wedge 2+ sqrt{3} extgreater 1 Rightarrow (sqrt{6} +2)(2+ sqrt{3}) extgreater 1 Rightarrow cfrac{a}{b} extgreater 1 Rightarrow a extgreater b[/latex] SPOSÓB II [latex]a= sqrt{6} +2\ b=2- sqrt{3}\\\ 2,44 extless sqrt{6} extless 2,45\\ 2,44+2 extless sqrt{6}+2 extless 2,45+2\\ 4,44 extless sqrt{6}+2 extless 4,45}\\ underline{4,44 extless a extless 4,45}\\\ 1,73 extless sqrt{3} extless 1,74\\ -1,74 extless -sqrt{3} extless -1,73\\ 2-1,74 extless 2-sqrt{3} extless 2-1,73\\ 0,26 extless 2-sqrt{3} extless 0,27\\ underline{0,26 extless b extless 0,27} [/latex] ostatecznie [latex]0,26 extless b extless 0,27 extless 4,44 extless a extless 4,45}\\ b extless a[/latex] tada

Dodaj swoją odpowiedź